Europe taking the lead in responsible globalisation - Karl Aiginger; Heinz Handler (Kiel Institute for the World Economy (IfW), 2017)
Political opposition to globalisation has risen in industrialized countries, although the positive overall effects on the growth of the world economy and the alleviation of poverty are empirically verifiable. However, the effects of globalisation vary according to regions, professional groups, and education. In the period of intensive globalisation, unemployment and inequality have risen, and people feel their lives to be determined by forces they cannot influence. Since the many new challenges, such as climate protection, can be better solved by worldwide efforts, it is indispensable to avoid new national barriers and to strengthen the endorsement of globalisation and the concomitant welfare effects. However, it is also necessary to respect cultural differences in preferences and to view globalisation as a search and learning process. Instruments for the implementation of such a strategy may vary according to regional specifics. Social and ecological goals - gaining higher importance with rising per capita incomes - are well-represented in the European model, but for worldwide solutions other socio-economic models will offer preferences and solutions. Apart from the announced partial withdrawal of the United States from globalisation and the upcoming dominance of China in world affairs and large scale investment, Europe would be well-advised to take a greater responsibility if not the lead in determining the rules of globalisation. Based on an opinion-forming process within Europe, responsible globalisation can significantly improve the quality of life in Europe and its partners worldwide.
Keywords: E02; E61; F13; F42; O10; 330; responsible globalization; change in US policy; Chinese ambitions